2013
DOI: 10.1007/s11060-013-1114-6
|View full text |Cite
|
Sign up to set email alerts
|

Primary intracranial germ-cell tumors in adults: a practical review

Abstract: Primary intracranial germ-cell tumors are rare tumors primarily of adolescence, and literature on this disease in adults is scarce. The available evidence on intracranial germ-cell tumors is reviewed with a focus on adult patients whenever possible, and used to make suggestions for diagnosis and treatment. Diagnostic and treatment algorithms were developed to provide an evidence-based backbone to base treatment on in adult patients with a (suspected) primary intracranial germ-cell tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 58 publications
(99 reference statements)
0
21
0
Order By: Relevance
“…MRI demonstrates soft tissue masses with isointense or slightly hyperintense signals in T1 weighted images, which may be accompanied with calcification or cyst formation in T2 weighted images (22). Definitive diagnosis of GCT is performed through the histopathology approach: The majority of GCTs demonstrate immunohistochemical staining for placenta-like alkaline phophatase and c-Kit, otherwise known as CD117, which is an important mitogen for normal germ cells (11). Unfortunately, a biopsy is not possible for patients where the tumor location is inaccessible.…”
Section: Discussionmentioning
confidence: 99%
“…MRI demonstrates soft tissue masses with isointense or slightly hyperintense signals in T1 weighted images, which may be accompanied with calcification or cyst formation in T2 weighted images (22). Definitive diagnosis of GCT is performed through the histopathology approach: The majority of GCTs demonstrate immunohistochemical staining for placenta-like alkaline phophatase and c-Kit, otherwise known as CD117, which is an important mitogen for normal germ cells (11). Unfortunately, a biopsy is not possible for patients where the tumor location is inaccessible.…”
Section: Discussionmentioning
confidence: 99%
“…[1] However, the immunohistochemical expression of HCG-β had been detected in various tumors other than GCTs, including cystic pituitary adenomas, Rathke's cleft cysts, and craniopharyngiomas. [2310] In this case, we could not distinguish a craniopharyngioma from a GCT by the detection of HCG-β in the CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of intensive chemotherapy for malignant intracranial germ cell tumor have shown that NGGCT is highly responsive to chemotherapy and demonstrate a 5-year overall survival rate (OS) of nearly 60%-75% for patients treated with chemotherapy without irradiation at initial therapy (most of the patients were subsequently treated with radiotherapy); nevertheless, chemotherapy alone results in a higher relapse rate than chemotherapy combined with radiotherapy, indicating that irradiation should be included in treatment regimens. 4,6 Bromberg et al 3 reviewed the recent literature for intracranial germ cell tumor and reported that radiotherapy combined with platinum-based chemotherapy was effective and should represent the current standard for intracranial NGGCT. Neoadjuvant chemoradiotherapy is also an effective strategy, as Kochi et al 8 treated 11 patients with NGGCT using neoadjuvant chemotherapy with platinum-based agents (CE, PE, or ICE) and radiotherapy and reported that the 5-year progression-free survival rate and 5-year OS were both 90.9%.…”
Section: Chemotherapymentioning
confidence: 99%